Мовленнєві тактики реалізації стратегії дискредитації (на матеріалі промов дипломатів США) - Судус, Юлія (Lesya Ukrainka Eastern European National University, 2016)
The article presents the analysis of the accusation tactics that implement a discrediting strategy in the English diplomatic discourse. The aim of the article is to study speech act formations in tactics of accusation that implement a discrediting strategy. The object of the study is tactics of accusation, which implement the discrediting strategy in diplomatic discourse. The article offers a classification of markers of the communicative tactics of accusation that implement a discrediting strategy in the public statements of US diplomats, namely V. Nuland, G. Pyatt, S. Power, D. Baer, relating to the military conflict in eastern Ukraine. The total number of public speeches that have been analyzed is 97 (from 2013 to 2015). Attention is drawn primarily to the speech acts and how they implement the tactics of accusation in DD. The author has found that the tactics of accusation is basic and the most common tactics of implementing the discrediting strategy in the studied speeches. At the core of these tactics are mainly direct assertive speech acts. У статті автор аналізує тактику звинувачення, що реалізує стратегію дискредитації в англомовному дипломатичному дискурсі, а саме у промовах В. Нуланд, Дж. Пайєтта, С. Пауер, Д. Байєра за 2013–2015рр., які стосуються військового конфлікту на сході України. Встановлено, що тактика звинувачення є однією з найпоширеніших тактик реалізації стратегії дискредитації в досліджуваних промовах. Автор робить спробу виокремлення маркерів тактики звинувачення в дипломатичному дискурсі. В основі зазначеної тактики – прямі асертивні мовленнєві акти.
Keywords: дипломатичний дискурс; стратегія дискредитації; конфронтативна стратегія; тактика звинувачення; прямий мовленнєвий акт; diplomatic discourse; discrediting strategy; confrontational strategy; tactics of accusation; direct speech act